La protección de datos personales crediticios y la administración del perfil de riesgo en Ecuador - Mancero Gavilanes, Susana Lucia (2025)
The research analyzes the regulations concerning data protection in the Ecuadorian financial system, highlighting the importance of proper management of individuals’ financial information. It discusses various types of data, including credit data due to its extensive scope. Financial institutions must comply with very strict measures to protect personal data, which includes obtaining the authorization of the owner's data before processing. Additionally, it is mentioned that the lack of credit reports affects risk outlining, leading institutions to develop more rigorous internal processes for analysis. The objective of this study is to develop a critical legal analysis of the relationship between the protection of personal credit data and the violation of the financial system entity’s right to manage its own risk profile in Ecuador. According to the research approach, it is a qualitative study through a documentary analysis of current laws and regulations. Finally, it also addresses the responsibility of credit bureaus, the limitations, and the handling of personal information to avoid the violation of rights. It is said that current regulations are effective in terms of data protection, but there are still challenges, especially in raising awareness with clients.